Os universais em Abelardo: suas críticas ao realismo e sua solução nominalista para o problema - Nobrega, Jonas Da [UNIFESP] (2021)
In this thesis, I investigate Abelard’s arguments about three doctrines dealing with universals in his period (12th century) – according to them, universals are things (res) – and his solution to the problem – according to which universals are words. For this, I analyze Abelard’s twenty-two arguments in his Logica “Ingredientibus” and Logica “Nostrorum petitioni sociorum” against realist doctrines, according to which universals are things (a res, understood as an essence, a collection or a convergence of individuals). After this, I analyze Abelard’s solution to the problem, according to which universals are words, and how this solution is related to his notion of individuals’ status. In these works by Abelard, I also analyze how he describes the concept produced by the thought of those who hear a common noun. Through these analyses, I formulate and demonstrate two hypotheses: that the Abelardian status has an equivalent role to the universal res in realist doctrines, and that Abelard, in the mentioned works, develops only one theory about the meaning of common nouns, despite the use of different arguments for doing so.